Please please please help
Please please please help - 1

Answers

Answer 1
Answer:

Answer:

Isosceles

Step-by-step explanation:

If BD is an altitude, it splits triangle ABC into 2 triangles.  It is also a median, so it splits the angle ABC into 2 congruent angles.  Angle ABD and CBD are congruent.  That means that angles A and C are congruent. This is true because the 2 angles at D are both right angles.  Because of this, side AB and side CB are congruent.  That means that this is an isosceles triangle.  


Related Questions

Ms. Leong owned an ice cream store and had chocolate and vanilla ice cream for sale. She sold 3/4 of the chocolate ice cream and 1/2 of the vanilla ice cream. If she had 20 scoops of chocolate ice cream and 30 scoops of vanilla ice cream left, how many scoops of ice cream did Ms. Leong have altogether at first?
Mrs. Rosso has to travel 390 miles on a highway. She drives 130 miles in 2 hours. If she 7 hours to travel at that rate, will she arrive at her destination on time?
Three friends are selling items at a bake sale. May make $23.25 seeking bread. Inez sells gift baskets and makes 100 times as much as May. Carolyn self pies and make one tenth of the money Inez makes. How much money does each friend make.
The top and bottom margins of a poster are each 15 cm and the side margins are each 10 cm. If the area of printed material on the poster is fixed at 2400 cm2, find the dimensions of the poster with the smallest area.--------- cm (width)--------- cm (height)
The quadratic equation y=-0.5x+4x+10 models the path of a heavy ball through the air, where y represents the height in feet and x represents time in seconds. When will the ball hit the ground?

Review important identitie
cosx cosy = 1/2 [cos(x+y) + cos(x−y)]

Answers

cos(x+y) = cosxcosy - sinxsiny;
cos(x-y) = cosxcosy + sinxsiny;
..................................................
=> cos(x+y) + cos(x-y) = 2cosxcosy =>cosx cosy = 1/2 [cos(x+y) + cos(x−y)];
cosxcosy=(1)/(2)\left[cos(x+y)+cos(x-y)\right]\n\nR=(1)/(2)\left(cosxcosy-sinxsiny+cosxcosy-sinxsiny\right)\n\n=(1)/(2)\cdot2cosxcosy=cosxcosy=L\n\nR=L

Accumulated depreciation of a particular plant asset refers to: half-yearly depreciation total depreciation. or neither?

Answers

Accumulated depreciation of a particular plant asset refers to neither the half-yearly depreciation nor total depreciation.

Accumulated depreciation is the total depreciation expense reported since the plant asset was bought. Its amount is used to determine the book value or carrying value of the plant asset. 

When the plant asset is fully depreciated, that is only the time when accumulated depreciation is equal to the total depreciation.

What is the factored form of 6x^2 + 13x + 6?A.) (x + 4)(x + 9)
B.) (2x + 3)(3x + 2)
C.) (2x + 6)(3x + 1)
D.) (6x + 1)(6x + 1)

Answers

The answer would be B.first you would have to multiply the first coefficient,6 with the last term. being 6,                                                                                                   6·6 = 36.Now there is a few factors such as 1,2,3,4,6,9,12,18,36, and the negatives of these numbers, but i wont list them,i will just use the numbers i need for this problem.so i will replace the number 13 in this equation.              [6ײ+4×]+[9×+6]. then i will factor the GCF 2 into the first group and then factor 3 in the second group. 2×[3×+2]+3·[3×+2]. then i would have to factor out the two numbers out of the term 3×+2 then combine the like terms making the equation [2×+3]·[3×+2] making the answer B. Hope i helped bye.

The correct answer is option B.) (2x + 3)(3x + 2).

Given that the factored form of 6x^2 + 13x + 6 is equivalent to which of the following.

A.) (x + 4)(x + 9)

B.) (2x + 3)(3x + 2)

C.) (2x + 6)(3x + 1)

D.) (6x + 1)(6x + 1)

To determine the factored form of the quadratic expression 6x^2 + 13x + 6, we can apply the factoring technique. We are looking for two binomials in the form (px + q)(rx + s) that, when multiplied, result in the original expression.

To factor the expression, we need to find two numbers whose product is equal to 6 * 6 = 36 and whose sum is equal to 13.

The numbers that satisfy these conditions are 4 and 9.

Therefore, the factored form of the expression is:

(2x + 3)(3x + 2)

So, the correct answer is option B.) (2x + 3)(3x + 2).

Learn more about factoring quadratic expressions click here: brainly.com/question/14680354

#SPJ6

Use differentials to find an approximate value for \sqrt[3]{65}

Answers

: Let y = f(x) =  x^1/3  
Then dy = 1/3*x^(−2/3) dx 
 Since f(64) = 4.
We take x = 64 and dx = ∆x = 1  
This gives dy = 1/3*(64)^(−2/3)* (1) =  1/48  
∴65^(1/3) = f(64 + 1) ≈ f(64) + dy = 4 + 1/48 ≈ 4.021 

Answer:

: Let y = f(x) =  x^1/3  

Then dy = 1/3*x^(−2/3) dx 

 Since f(64) = 4.

We take x = 64 and dx = ∆x = 1  

This gives dy = 1/3*(64)^(−2/3)* (1) =  1/48  

∴65^(1/3) = f(64 + 1) ≈ f(64) + dy = 4 + 1/48 ≈ 4.021 

Read more on Brainly.com - brainly.com/question/19668#readmore

Step-by-step explanation:

68 days increased by 75%

Answers

68×75=5100
5100÷100=51
68+51=119

answer-119
hope it helps

Holly, the author, has written 160 pages of her next book. She needs to write a minimum of 20 pages per day to complete the expected 380 page book. Which inequality below expresses this situation?

Answers

Answer:

days  ≤ 6

Step-by-step explanation:

she gas 160 pages out of the 380 pages, so she needs to write other:

380 - 160 = 120 pages.

If she writes a minimum of 20 pages per day, then the maximum number of days in which she will finish the book is:

20*d = 120

d = 120/20 = 6

so d is the number of days, and we have that:

d ≤ 6.

The equality is when she only writhes 20 pages per day, and if she writes more than that, then the number of days needed will be smaller than 6.